Effects of a novel protease enzyme (CIBENZA DP100) on finishing pig growth performance and carcass characteristics - Ethan W Stephenson; Joel M DeRouchey; J Escobar; Jason C Woodworth; Michael D Tokach; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2014)
A total of 1,170 pigs (PIC 337 × 1050; initial BW 56.3 lb) were used in a 131-d study to determine the effects of a protease enzyme on growth performance and carcass characteristics of finishing pigs. Dietary treatments consisted of: (1) a positive control diet formulated to provide 90% of the standardized ileal digestible (SID) lysine requirement for these pigs; (2) a negative control diet formulated to provide 90% of the SID lysine requirement minus the expected nutrient release (both amino acids and dietary energy) from the protease enzyme (CIBENZA DP100, Novus International, Inc., St. Charles, MO), and (3) the negative control diet with the addition of 0.05% CIBENZA DP100. The diets were formulated such that the negative control diet containing the protease enzyme had calculated nutrient concentrations similar to the positive control. Pens of pigs were randomly allotted to 1 of 3 treatments with 26 pigs per pen and 15 replicates per treatment. Overall (d 0 to 131), pigs fed the positive control diet had increased (P<0.05) ADG compared with pigs fed the negative control diet. Pigs fed the negative control diet plus CIBENZA DP100 had improved (P<0.05) ADFI and a tendency for improved (P = 0.09) ADG compared with pigs fed the negative control diet without the enzyme. No differences were observed in ADG, ADFI, or F/G between pigs fed the positive control diet and those fed the negative control diet plus the protease enzyme, which suggests that the release values attributed to the enzyme are accurate. The only observed effect on carcass characteristics was for yield, in which the pigs fed the negative control diet with the enzyme had lower (P<0.05) carcass yield than pigs fed the negative control diet without the enzyme. Although differences did exist in feed cost per pig and feed cost per pound of gain, no differences were observed for income over feed cost (IOFC) between treatments. These data suggest that the protease enzyme CIBENZA DP100 will elicit improved growth performance when added to diets formulated at 90% of the pig's estimated SID lysine requirement.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Finishing pig; Carcass characteristics; Protease enzyme